Estudio de servicios de e-comunicación y productos ciberperiodísticos en la prensa digital mexicana 2008 - López Aguirre, José Luis (Revista General de Información y Documentación, 2009)
The periodistic products and communication services that provide new media that emerge in virtual space are a proof of the adaptation and innovation capacity throughout continuous changes and exigence presented by the actual media scenario. In the present study we will try to identify the different gamut of e- Communication services and cyber periodistic products that were taken out of the selected sample of Mexican cybermedia. The aim of this study is to evaluate how the online Mexican press, particularly digital newspapers and news portals, have used the technological means and characteristics of the digital environment to satisfy the informative and communicative needs of its users.
Keywords: Periodistic products; Communication services; Online newspapers; Cybermedia; Cyberjournalism; Digital journalism; Digital press